2019
DOI: 10.1177/0963721419867099
|View full text |Cite
|
Sign up to set email alerts
|

Distractor Ignoring: Strategies, Learning, and Passive Filtering

Abstract: Our sensory environments contain more information than we can process, and successful behaviors require the ability to separate task-relevant information from task-irrelevant information. Much research on attention has focused on the mechanisms that result in selection of desired information, but much less is known about how distracting information is ignored. Here, we describe evidence that strategic, learned, and passive information can all contribute to better distractor ignoring. The evidence suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 45 publications
(61 reference statements)
2
104
0
Order By: Relevance
“…It is currently actively debated whether distractor inhibition is under similar flexible top-down control as target facilitation and depends on representation in working memory. 6,9,14 A large body of work shows a close relationship between selective attention and visual working memory, such that attention is directed toward visual information that is actively represented in working memory. 1,23 Indeed, many studies have demonstrated that the content of working memory automatically biases attention toward matching incoming information, even when that information is known to be detrimental to performance at the current task.…”
Section: Preparatory Distractor Suppressionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is currently actively debated whether distractor inhibition is under similar flexible top-down control as target facilitation and depends on representation in working memory. 6,9,14 A large body of work shows a close relationship between selective attention and visual working memory, such that attention is directed toward visual information that is actively represented in working memory. 1,23 Indeed, many studies have demonstrated that the content of working memory automatically biases attention toward matching incoming information, even when that information is known to be detrimental to performance at the current task.…”
Section: Preparatory Distractor Suppressionmentioning
confidence: 99%
“…In this, we dissociate between proposed preparatory mechanisms that suppress distractor features in advance and suppressive mechanisms that come about in response to distracting sensory input . While the long‐standing view has been that inhibition of distracting or irrelevant sensory information is under direct, volitional control similar to attention to goal‐relevant aspect of the environment, it is becoming increasingly clear that suppression is not under direct top‐down control and can be implemented via a multitude of underlying mechanisms, each tuned to specific circumstances . Recent behavioral studies, for example, have shown that the ability to ignore distracting information often strongly depends on learning based on previous experiences with the distracting information .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations